PENERAPAN PENDEKATAN PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Fatimah, Ghina Nur'aini; Setiawan, Wahyu; Kadarisma, Gida (IKIP Siliwangi, 2023)
The purpose of this study was to determine the improvement of student learning outcomes in learning mathematics on the material of straight line equations using the Problem Based Learning approach. This research method is Classroom Action Research (CAR) which is carried out through 2 cycles. The research subjects were 19 students of SMP Negeri 16 Cimahi class VIII C. To obtain research data used instruments in the form of essay tests, interviews, and observation questionnaires. The data analysis technique used in this research is qualitative. The results showed an increase in learning outcomes, in the first cycle students whose scores reached the KKM were 10 students (52.63%), in the second cycle there were 16 students (89.47%), besides that when learning was carried out students were more active in asking questions, and discuss. Thus, it is concluded that the Problem Based Learning approach can improve learning outcomes and student activity in learning the material of Straight Line Equations.